2016
DOI: 10.1007/s12223-016-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence factors and phylogenetic group determination of Escherichia coli isolated from diarrheic and non-diarrheic calves from Brazil

Abstract: This study aimed to detect virulence factors, pathovars, and phylogenetic groups of Escherichia coli strains obtained from feces of calves with and without diarrhea up to 70 days old and to determine the association between occurrence of diarrhea, phylogenetic groups, and pathovars. Phylo-typing analysis of the 336 E. coli strains isolated from calves with Clermont method showed that 21 (6.25 %) belong to phylogroup A, 228 (67.85 %) to phylogroup B1, 2 (0.6 %) to phylogroup B2, 5 (1.49 %) to phylogroup C, 57 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
4
15
1
Order By: Relevance
“…Overall, 65% (126/195) CFUs analysed belonged to commensal phylo-group B1, corresponding to the animals' healthy status. As in the world literature (Son et al, 2009;Tenaillon et al, 2010;Bessalah et al, 2016;Coura et al, 2017;Souto et al, 2017) we also found the predominance of B1 phylo-group (40/65 CFUs; 61Á5%) in calves, followed by E (13/65; 20%). Similarly, B1 (33/65 CFUs; 50Á8%) predominated in foals, followed by E (14/65 CFUs; 21Á5%) and C (10/65 CFUs; 15Á4%), being a profile previously reported in healthy horses (Smati et al, 2015).…”
Section: Resultssupporting
confidence: 88%
“…Overall, 65% (126/195) CFUs analysed belonged to commensal phylo-group B1, corresponding to the animals' healthy status. As in the world literature (Son et al, 2009;Tenaillon et al, 2010;Bessalah et al, 2016;Coura et al, 2017;Souto et al, 2017) we also found the predominance of B1 phylo-group (40/65 CFUs; 61Á5%) in calves, followed by E (13/65; 20%). Similarly, B1 (33/65 CFUs; 50Á8%) predominated in foals, followed by E (14/65 CFUs; 21Á5%) and C (10/65 CFUs; 15Á4%), being a profile previously reported in healthy horses (Smati et al, 2015).…”
Section: Resultssupporting
confidence: 88%
“…Similar data were obtained in the study carried from Minas Gerais state, Brazil. Coura et al (2017) demonstrated that STEC and EHEC isolates from healthy and diarrheic calf feces belonged mainly to phylogenetic groups B1 and A.…”
Section: Resultsmentioning
confidence: 99%
“…The association of eae‐ positive STEC with animal disease was reported by some authors (Martins et al ; Leomil et al ; Salvadori et al ), whereas many others described similar frequencies both in diarrheic and non‐diarrheic animals (Aidar‐Ugrinovich et al ; Timm et al ; Coura et al ), reinforcing that only some strains are able to cause disease.…”
Section: Virulence Of Stec Isolated From Animalmentioning
confidence: 70%
“…STEC strains are frequently ehxA‐ positive, with frequencies varying from around 35% to as high as 90%, and it is generally similar among strains isolated from either diarrheic or healthy animals and from eae ‐positive or ‐negative STEC strains (Leomil et al ; Salvadori et al ; Vetoratto et al ; Joaquim et al ; Irino et al ; Aidar‐Ugrinovitch et al ; Farah et al ; Oliveira et al ; Pigatto et al ; Beraldo et al ; Maluta et al ; Martins et al ; Gonzalez et al ). However, Coura et al () detected this gene only among eae ‐positive strains isolated from calves, both diarrheic and healthy ones. However, some studies described lower frequencies or even the absence of this gene (Moura et al ; Ferreira et al ; Coura et al ).…”
Section: Virulence Of Stec Isolated From Animalmentioning
confidence: 99%
See 1 more Smart Citation